Corrosion monitoring on steel reinforced nano metaclayed-UHPC towards strain modulation using fiber Bragg grating sensor - Mohd Faizal, Md Jaafar (IOP Publishing, 2018)
Today, research on steel corrosion issues are still widely debated and revived scientific attention. In order to detect steel corrosion, an idea to explore the relationship of corrosion potential using half-cell potential related to the variations in strain change on embedded steel measured by FBG sensor were explored. In this study, the steel was embedded in various types of concrete consist of NPC, HPC, UHPC and a series of nano metaclayed-UHPC. It was observed that the steel embedded in NPC is very low in corrosion resistance. Conversely, nano metaclayed-UHPC can delay the embedded steel to corroded. It was also noticeably that the corrosion readings for steel embedded in NPC specimens possess the highest possibility of corrosion potential as well as the large strain was observed by using FBG. Inclusion of 1% nano metaclay in UHPC shows a superior performance in term of corrosion resistance and protected the steel from corrosion. The RSM analysis was found that the R2 values are strong relationship between corrosion potential and strain changes. The R2 obtained for NPC, HPC, UHPC, UHPC1, UHPC3 and UHPC5 models associated with corrosion potential with respect to strain changes were found to be 0.95, 0.99, 0.87, 0.93, 0.98 and 0.97, respectively.